(untitled) (Research, Society and Development, 2022)
Formed by a diverse and numerous professional category, health workers are exposed to occupational risks arising from long working hours, high levels of stress and sleep deprivation. Such working conditions also influence the health and quality of life of professionals enrolled in multi-professional residency programs. Therefore, the objective is to analyze the scientific evidence about the health of multiprofessional health residents. This is an integrative literature review carried out in September 2021 in the LILACS, SCOPUS and MEDLINE databases, based on the analysis of articles published between 2005 and 2021. The following descriptors were used: internship and residency, non-medical internship, worker health and health. Twelve studies were included that showed the prevalence of female residents, aged between 20 and 30 years, single, without children and who entered residency programs between one or two years after graduation. Regarding the health of residents, studies reveal a prevalence of anxiety, stress and depression, decreased sleep quality and quality of life. Although it is considered the best form of professional qualification, the training period of the multiprofessional residency is characterized as a moment that causes too much physical and emotional exhaustion. From this perspective, residency can increase the risk of health problems that affect the quality of life of residents, which requires the development of actions that promote their health.